Feto-maternal outcome in pregnancies with preterm premature rupture of membranes: a tertiary hospital experience - D’souza, Aparajita Sophia; Walia, Moneet; Gupta, Garima; Samuel, Clarence; Katumalla, Francis Sridhar; Goyal, Sunitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm premature rupture of the membranes (PPROM) is a known dreaded complication of pregnancy as it is associated with significant perinatal complications. The objective of our study was to bring forward the incidence and feto-maternal outcome in pregnancies with PPROM in Indian scenario. Methods: This retrospective cohort study was conducted in the Department of Obstetrics and Gynecology, in a tertiary hospital in Punjab between January 2014 and December 2014. Medical records of all pregnant patients who were admitted to our department with PPROM on the basis of clinical and /or laboratory data were reviewed. These 75 women were divided into two groups according to gestation age (GA), Group 1- early PPROM (24- 33 6/7 weeks of GA) (n=38) and Group 2- late PPROM (34-36 6/7 weeks of GA) (n=37). A multivariate analysis was used to find the association between PPROM and perinatal outcome. Results: During the study period, there were 1528 deliveries in the hospital and 75 pregnant women were diagnosed to have PPROM giving an overall incidence of 4.9%. In both the groups most common maternal complication was chorioamnionitis (15.7% vs. 2.7%) and most common neonatal complication was physiological jaundice (56.8% vs. 69.2%). Most of the babies required phototherapy (50% vs. 43.5%) and antibiotics. Our study demonstrated that patients in group 1 had significant increase in the frequency of chorioamnionitis, hyaline membrane disease, septicaemia, periventricular leukomalacia, intrauterine pneumonia, need for ventilator support and inotropes. Patients in group 2 had significant increase in the frequency of APGAR score <7 at 1 min, APGAR <7 at 5 min and LSCS rate. Conclusions: The study result implies that lesser the gestation age more are the chances of fetomaternal complications in patients with PPROM. Early PPROM is associated with higher rates of perinatal morbidity and mortality.